History and Development of Packaged Explosives Progressing from Nobel's Inventions to the Recent Introduction of Emulsions - Robert B. Hopler (International Society of Explosives Engineers, 1991)
"The story of packaged explosives begins with the use of black powder (also called gunpowder) in mining. Although discovered in the 13th century, it was not until 1627 that the first records of use in mining is recorded. It took until the early 1800's before its use began in underground coal. Althougha free-running, granular material, its recommended (and safest) manner of use was for the miner to pour it into ready-made or onsite formed paper bags prior to insertion into the borehole. This was absolutely necessary in horizontal or upward-slanting holes."